2018
DOI: 10.1186/s13613-017-0346-6
|View full text |Cite
|
Sign up to set email alerts
|

Oleic acid chlorohydrin, a new early biomarker for the prediction of acute pancreatitis severity in humans

Abstract: BackgroundThe early prediction of the severity of acute pancreatitis still represents a challenge for clinicians. Experimental studies have revealed the generation of specific halogenated lipids, in particular oleic acid chlorohydrin, in the early stages of acute pancreatitis. We hypothesized that the levels of circulating oleic acid chlorohydrin might be a useful early prognostic biomarker in acute pancreatitis in humans.MethodsIn a prospective, multicenter cohort study, plasma samples collected within 24 h a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 26 publications
0
37
0
1
Order By: Relevance
“…The medication review by a pharmacist before transferring the patient to the IU proved to be effective in reducing the number and severity of medications-related problems ( 49 ) , although the impact on outcomes such as mortality and readmission is inconclusive ( 14 , 49 ) . A recent study ( 61 ) found that medication reconciliation by a pharmacist reduced errors in medication transfer, potential adverse events, and related costs.…”
Section: Discussionmentioning
confidence: 99%
“…The medication review by a pharmacist before transferring the patient to the IU proved to be effective in reducing the number and severity of medications-related problems ( 49 ) , although the impact on outcomes such as mortality and readmission is inconclusive ( 14 , 49 ) . A recent study ( 61 ) found that medication reconciliation by a pharmacist reduced errors in medication transfer, potential adverse events, and related costs.…”
Section: Discussionmentioning
confidence: 99%
“…Franco-Pons et al [182] evaluated the generation of halogenated fatty acids in the areas of fat necrosis in rats and they concluded that during AP, adipose tissue release FA-CI, which exacerbated the SIRS. Based on these results, de-Madaria et al [183] evaluated the role of OAC in a prospective and multicenter cohort study as marker of the severity of AP. They concluded that OAC is generated during AP, its levels can be measured in plasma, and these correlate with AP severity.…”
Section: Oleic Acid Chlorohydrinmentioning
confidence: 99%
“…Only the chlorohydrin of oleic acid was present in plasma (10). In humans, we found that oleic acid chlorohydrin was an excellent early marker of moderate-tosevere disease (11).…”
Section: Discussionmentioning
confidence: 72%
“…Concerning the different types of UFAs, oleic acid is the more important MUFA, is the predominant fatty acid in human pancreatic extracts (23,32) and in human pancreatic necrotic collections (6,7). In vitro and laboratory animal studies suggest that oleic acid is associated with local and systemic toxicity (7,10,11,(33)(34)(35). In addition, in a study by Pironi et al in patients with parenteral nutrition, the administration of a lipid emulsion based on MUFA produces a higher inflammatory status than in patients using a fish-oil based lipid emulsion (36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation